Re-Placing Rural Education: AERA Special Interest Group on Rural Education Career Achievement Award Lecture - Michael Corbett (Journal of Research in Rural Education, 2021)
I would like to begin by acknowledging that the place from which I speak is Mi'kma'ki, the traditional and unceded territory of the Mi'kmaq people. This people will enter this story in due course. The colonial name for this place today is Nova Scotia, Canada, which evolved out of the original colonial place names this territory shares with the United States such as Acadie, British North America, and New France (Corbett, 2013, 2021a). These names represent the changing colonial hegemonies of which the Canadian state with its ten provinces and three territories is the latest incarnation. But there is an older name for the section of Turtle Island where I live and work, which is Mi'kma'ki.